Respons Pertumbuhan Dan Hasil Tanaman Kedelai Pada Konsentrasi Plant Growth Promoting Rhizobacteria (PGPR) Dari Akar Bambu (Bambusa sp.) - Mustafa, Putri Alfa; Paulus, Jeanne M.; Polii, Maria G.M. (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the response of soybean plants to the application of PGPR (Plant Growth Promoting Rhizobacteria) from bamboo roots and to obtain the best concentration of PGPR from bamboo roots to increase soybean growth and yield in Sendangan Village, Sonder District, Minahasa Regency. This research was conducted for 3 months, from July to October 2022. The data analysis method used in this study was Anova analysis (Analysis of Variance). The design of this study used a randomized block design (RBD) consisting of 5 treatments and 4 replications so that there were 20 plots, namely treatment P0 0 ml/water, P1 PGPR concentration 10 ml, P2 PGPR concentration 20 ml, P3 PGPR concentration 30 ml, P4 PGPR concentration 40 ml so that there are 20 plots. The variables observed were plant height, number of branches, number of pods, number of root nodules, and production per plot. The results showed that giving PGPR from 4 treatments P0 0 ml/liter of water, P1 10 ml/liter of water, P2 20 ml/liter of water, P3 30 ml/liter of water, and P4 40 ml/liter of water got the best concentration of PGPR bamboo roots at P3 30ml/liter of water, thereby increasing the growth and yield of soybeans.